Anti MÃ¼llerian Hormone (AMH) Level as Ovarian Reserve Marker before and after Cystectomy Laparotomy - Sahabuddin, Rosdiana; Abdullah, Nusratuddin; Manoe, IMS Murah (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To investigate the comparison of the Anti-Mullerian Hormone (AMH) as the ovarian reserve marker before and after cystectomy. Methods: This study used prospective cohort design which included all women with the ovarian cyst who underwent cystectomy laparotomy. The subjects were examined AMH level before and after the procedure. Data were analyzed using one- way Anova, T- paired test, and T-independent test with p value